Studies on multipurpose fodder trees and shrubs in West Africa: Variation in determinants of forage quality in Albizia and Paraserianthes species - Larbi, Asamoah; Smith, Jimmy W.; Adekunle, I.O.; Kurdi, I.O. (Springer, 1996)
We investigated variation in forage production, in sacco dry matter (DM) and nitrogen (N) degradations, and in vitro gas production characteristics of four Albizia (A. lebbeck N 864), A. procera N 865, A. saman N 825) and Paraserianthes falcataria (N 783) provenances obtained from The Nitrogen Fixing Tree Association. After one year of establishment forage production was assessed by harvesting trees at 0.5 m above ground in the main wet (April-August) minorwet (September-Novermber) and dry (December-March) seasons at Ibadan, southwestern Nigeria. Forage smaples from the main-wet and dry seasons were incubated for 6, 12, 48 72 and 96 h in rumen-fistulated cattle to estimate in sacco DM and N degradation characteristics. In vitro gas production was estimated over 3, 6 12, 24, 72 and 96 h of incubation. Forage producton A. procera was significantly higher than the other species in all seasons. Cell-wall components were comparatively higher in A. procera than the other species. Potential DM and N degradations of A. lebbeck and A. saman were significantly higher than falcataria and A. procera. The results suggest that A. lebbeck and A. saman provenances used in this study have relatively higher feed value than A. procera and falcataria.